Methodological aspect of formation of professional and pedagogical readiness for students’ training of basics of health - Семенець, Лариса Миколаївна (Pedagogy of Higher and Secondary Education, 2015)
Semenets L. M. Methodological aspect of formation of professional and pedagogical readiness for students’ training of basics of health. In the article the features of professional readiness formation of future teachers for students’ training of basics of health from the activity, system, comprehensive, person-centered, anthropological, cultural, acmeological and competence based approaches have been analysed.